Methods of Teaching English in Higher Education - Embergenova N. (Zien Journals, 2023)
The article is devoted to the consideration of various, in our opinion effective, ways of learning English. The publication discusses the possibilities of using copyright techniques that contribute to the rapid study of foreign languages, and in particular the English language.
Keywords: English; learning English; ways of learning English; copyright methods of learning English